Attitudes towards human milk banking among native turkish and refugee women residing in a rural region of Turkey: a mixed-methods approach - Ceren Varer Akpinar; Aliye Mandiracioglu; Safiye Ozvurmaz; Filiz Adana; Nazife Koc; Fatma Kurt (BMC, 2022)
Abstract Background Human milk banks (HMB) play an essential role by providing human milk to infants who would otherwise not be able to receive mother's milk. There is currently no donor milk bank in Turkey. For any new health intervention to be successful, determining its acceptability is a vital first step. This study intends to determine the opinions, knowledge, and attitudes of native Turkish and refugee women living in Çeştepe, Aydın, a rural area in Turkey, about HMB. Methods A population-based cross-sectional, mixed-methods study was conducted. Qualitative study data were collected through in-depth interviews with 33 women, and quantitative study data were collected using a questionnaire. A total of 271 women in the region were included in the study. Qualitative data were thematically analyzed and then a conceptual framework was created. Logistic regression was performed for quantitative data. Results Fifty-seven point nine per cent of the women were willing to donate breast milk, whereas only 27.7% were willing to use donor milk for their babies. Religious concerns, fear of infectious diseases, and distrust in people they did not know were among the reasons for the negative attitudes of the women. Fear of infectious diseases was mentioned specifically by native Turkish women, and religious concerns were reported both by native Turkish and refugee women. The importance of breast milk and religion were among the reasons for positive attitudes. Additionally, odds of having a positive attitude were 4.19 times higher in homemaker women (95% CI 2.0, 8.76); 4.77 times higher in women with three or more children (95% CI 1.25, 8.15); 6.12 times higher in women who had a positive attitude towards wet nursing (95% CI 3.14, 9.63); and 2.68 times higher in those who had previously heard about human milk banking (95% CI 1.24, 5.79). Conclusion Attitudes towards HMB are affected by religion, cultural beliefs, and concerns about the safety of breast milk in HMBs. Refugees and native Turkish women are found to have similar religious concerns. These findings should be taken into consideration in human milk banking initiatives and in activities to increase acceptance by the public.